2019
DOI: 10.1097/ccm.0000000000003892
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic- and Fluid-Focused Bundles Potentially Improve Sepsis Management, but High-Quality Evidence Is Lacking for the Specificity Required in the Centers for Medicare and Medicaid Service’s Sepsis Bundle (SEP-1)*

Abstract: Objective: To address three controversial components in the Centers for Medicare and Medicaid Service’s sepsis bundle for performance measure (SEP-1): antibiotics within 3 hours, a 30 mL/kg fluid infusion for all hypotensive patients, and repeat lactate measurements within 6 hours if initially elevated. We hypothesized that antibiotic- and fluid-focused bundles like SEP-1 would probably show benefit, but evidence supporting specific antibiotic timing, fluid dosing, or serial lactate requirements wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 51 publications
1
20
0
3
Order By: Relevance
“…Several investigators have questioned the use of the SEP-1 bundle and its association with patient outcomes, noting the need for additional evidence 18 19. Yet, all have failed to estimate the value of nurses—the clinicians who most often implement components of the SEP-1 bundle and actively monitor the status of these critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have questioned the use of the SEP-1 bundle and its association with patient outcomes, noting the need for additional evidence 18 19. Yet, all have failed to estimate the value of nurses—the clinicians who most often implement components of the SEP-1 bundle and actively monitor the status of these critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rigid care bundles such as SEP-1 that emphasize timeliness over accuracy may contribute to the Lactate monitoring is increasingly emphasized in current sepsis guidelines and quality measures despite a paucity of evidence that checking lactate levels improves outcomes. 1 Han and colleagues retrospectively observed that for patients with an initial elevated lactate, delays in subsequent lactate draws were associated with increased mortality and increased time to antibiotics. 2 However, this and other retrospective studies suffer from ascertainment bias whereby lactate measurements increase detection of cases with less clinical severity.…”
Section: Does Universal Lactate Screening Cause Unnecessary Antibiotic Prescribing?mentioning
confidence: 99%
“…In patients with suspicion for infection, but without clinical evidence of cardiovascular or biochemical insufficiency, a goal of 3 h may be more realistic and acceptable. [24] Unknown variables still exist, such as variations in biologic phenotypes, where the host-response pattern to intervention is not as predicted. [25]…”
Section: Early Intervention: Friend or Foe?mentioning
confidence: 99%